Tomografia computadorizada de feixe cônico na odontologia de cães e gatos - ROZA, Marcello Rodrigues da (2009)
Eleven dogs and four cats with buccodental alterations, treated in the Centro Veterinário do Gama, in Brasilia, DF, Brazil, were submitted to cone beam computed tomography. The exams were carried out in a i-CAT tomograph, using for the images acquisition six centimeters height, 40 seconds time, 0,2 voxel, 120 kilovolts (kV) and 46,72 milliampéres per second (mAs). The ideal positioning of the animal for the exam was also determined in this study and it proved to be fundamental for performing the exam, which required a simple and safe anesthetic protocol due to the relatively short time necessary in obtaining the images. Many alterations and diseases had been identified, with extreme accuracy of the images, becoming the cone beam computed tomography as a safe, accessible and feasible imaging method which could be included in the small animals dentistry routine diagnosis